Identifying mothers and fathers of children in care using linked administrative data - Warner, Nell (International Journal of Population Data Science, 2025)
Objectives There are challenges carrying out administrative data research on parents of children in the care system, particularly fathers, because of difficulties in linkage. This paper compares methods to link to parents using different datasets. Methods Children who entered care in Wales between 2005 and 2019 were identified from Looked After Children data. This was linked to The Children and Family Court Advisory and Support Service data to identify parents involved in public and private law cases. The 2011 and 2021 Census were used to identify if children were resident with parents on census dates. Welsh Demographic Service Data was also used to identify adults who the children were resident with fathers before care entry and National Community Child Health Database was use to identify biological mothers. The linkage rates and potential biases were assessed. Results All methods enable some parents/parental figures to be identified, but linkage to fathers remains a problem for the majority of research designs. Response rate to the 2011 and 2021 Census’ were lower than for the general population and limits its use with this population. NCCH is useful for identifying biological mothers, but fathers can only be identified through CAFCASS Cymru for limited numbers of children. WDSD can identify adults resident with children on specific dates. Conclusion WDSD provides a good source of data for resident adults, but studies of non-resident fathers may have to be limited to children who have been involved in public or private law cases.